Praet, Stijn, and Anna Kérchy, eds. The FairyTale Vanguard: Literary Self-Consciousness in a Marvelous Genre. Newcastle upon Tyne: Cambridge Scholars, 2019. 290 pp. - Rusvai, Mónika (FOCUS: Papers in English Literary and Cultural Studies, 2020)
Every single book analyzing literary fiction that might attract a younger audience seems to begin with a disclaimer: yes, we know that this can be read by children, and no, we do not think it does not deserve serious critical attention. The Fairy-Tale Vanguard is no exception, but it courageously leaves the apologetic tone of earlier works and adopts an entirely professional attitude. The volume promises to reveal that fairy tales have always had their embedded potential in being able to express literary self-consciousness long before it was made mainstream through postmodern literature. As editor Stijn Praet observes in the introduction, this self-consciousness relies on both metaliterary reflection and literary experimentation. In his view, the fairy tale is an essentially protean genre, and a deeper look into its high fictionality and opaque textuality will definitely contribute to a wider acceptance of this often marginalized field of research.